Stand structure and breeding birds: Implications for restoring ponderosa pine forests. Issue 6 (16th July 2013) - Kalies, Elizabeth L.; Rosenstock, Steven S.
ABSTRACT: Fire‐adapted forests in the western United States have dramatically departed from the natural or evolutionary environment over the past century because of fire suppression, logging, grazing, and other management practices. In particular, most southwestern ponderosa pine ( Pinus ponderosa ) forests are characterized by dense stands of small‐diameter trees that are susceptible to stand‐replacing crown fires and ensuing damage to watersheds, wildlife habitat, and communities at the wildland‐urban interface. Restoration treatments using mechanical thinning and prescribed fire have become the dominant management paradigm in this forest type, with landscape‐scale projects being implemented over the next 20 years. Although many studies have examined wildlife responses to restoration treatments, single‐species information is difficult for managers to synthesize and incorporate into management decisions made at large scales. Our goal was to investigate responses of breeding birds in ponderosa pine forests to forest stand characteristics modified by restoration treatments. We sampled birds in 23 stands for 3 years in northern Arizona, and used multi‐season and multi‐species occupancy models to determine relationships between avian occupancy and stand attributes affected by treatment. Increasing occupancy rates and species richness were associated with decreasing canopy cover, increasing density of mature trees, and increasing density of snags. Occupancy rates and species richness were negatively associated with quadratic mean diameter, medium‐sized trees, and downed woody material. Associations of the avian community and individual species with herbaceous cover and tree clumping were less consistent. Our results support the implementation of forest restoration treatments for restoring avian community occupancy in ponderosa pine forests, and emulating the evolutionary environment is likely the best approach. We recommend reducing canopy cover via thinning, and retaining trees >45.7 cm diameter at breast height and snags. A commonly‐proposed diameter cap for retaining large trees after thinning (40.6 cm dbh) seems unlikely to benefit nesting passerines, as resulting tree densities would remain too large. We recommend occupancy modeling as an efficient method for assessing wildlife‐habitat relationships at large scales. © 2013 The Wildlife Society.